Stabilitas Reaktor Uplow Anaerobic Sludge Blanket-Hollow Centered Packed Bed dalam Produksi Biogas pada Kondisi Ruangan - Dana Sembiring, Surya; Irvan; Trisakti, Bambang; Novita Sari Sihombing, Dewi (Talenta Publisher (Universitas Sumatera Utara), 2019)
Anaerobic digestation was the docomposition of microbes from organic matter into methane, carbon dioxide, organic nutrients and compost in oxygen depletion and hydrogen gas. This study aimed to obtain the stability of the Uplow Anaerobic Sludge Hollow Centered Packed Bed reactor in biogas production at an ambient state that was seen through pH and alkalinity parameters. The process was carried out by varying hydraulic retention time, ei 45 days, 25 days, 10 days and 6 days with pH maintained 7 (Â±0,2). Analysis of pH and alkalinity was carried out to assess the stability of the reactor at ambient conditions using samples taken from the reactor overflow. The pH profile produced was relatively stable with a pH range between 5.8 - 7.2. The resulting alkalinity value was relatively stable with a pH range between 2,000-4,000 mg/L. The volume of biogas produced was 470 ml with concentration of methane (CH4), carbon dioxide (CO2) and trace hydrogen sulfide (H2S) respectively by 88.00%, 11.00% and 0.10%.